Education in Biomedical and Health Informatics in the Web 3.0 Era: Standards for Data, Curricula, and Activities - Otero, P.; Hersh, W. (Yearbook of Medical Informatics, 2011)
Web 3.0 is transforming the World Wide Web by allowing knowledge and reasoning to be gleaned from its content.Describe a new scenario in education and training known as “Education 3.0” that can help in the promotion of learning in health informatics in a collaborative way.Review of the current standards available for curricula and learning activities in in Biomedical and Health Informatics (BMHI) for a Web 3.0 scenario.A new scenario known as “Education 3.0” can provide open educational resources created and reused throughout different institutions and improved by means of an international collaborative knowledge powered by the use of E-learning. Currently there are standards that could be used in identifying and deliver content in education in BMHI in the semantic web era such as Resource Description Format (RDF), Web Ontology Language (OWL) and Sharable Content Object Reference Model (SCORM). In addition, there are other standards to support healthcare education and training. There are few experiences in the use of standards in e-learning in BMHI published in the literature.Web 3.0 can propose new approaches to building the BMHI workforce so there is a need to build tools as knowledge infrastructure to leverage it. The usefulness of standards in the content and competencies of training programs in BMHI needs more experience and research so as to promote the interoperability and sharing of resources in this growing discipline.
Keywords: Competency-based education; medical Iiformatics education; educational technology; health personnel; semantics